The effect of porosity and microcracking on the thermomechanical properties of cordierite. Issue 16 (December 2015) - Shyam, A.; Bruno, G.; Watkins, T.R.; Pandey, A.; Lara-Curzio, E.; Parish, C.M.; Stafford, R.J.
Abstract: The effect of porosity and microcracking on the mechanical properties (strength, fracture toughness, Young's modulus, and fracture energy) and thermal expansion of diesel particulate filter (DPF) grade cordierite materials has been investigated. A method to deconvolute the effect of porosity and microcracking on Young's modulus is proposed. In addition, the microcrack density and the pore morphology factor are calculated by applying a micromechanical differential scheme. The values of the investigated mechanical properties are shown to decrease with an increase in porosity, but the thermal expansion values are insensitive to porosity. The variation in mechanical properties as a function of porosity leads to distinct porosity dependence of thermal shock resistance for crack initiation and crack propagation for DPF grade synthetic cordierite.